Transcriptome Reprogramming of Symbiodiniaceae Breviolum minutum in Response to Casein Amino Acids Supplementation - Kirk, Andrea L.; Clowez, Sophie; Lin, Fan; Grossman, Arthur R.; Xiang, Tingting (Frontiers in Physiology, 2020)
Dinoflagellates in the family Symbiodiniaceae can live freely in ocean waters or form a symbiosis with a variety of cnidarians including corals, sea anemones, and jellyfish. Trophic plasticity of Symbiodiniaceae is critical to its ecological success as it moves between environments. However, the molecular mechanisms underlying these trophic shifts in Symbiodiniaceae are still largely unknown. Using Breviolum minutum strain SSB01 as a model, we showed that Symbiodiniaceae go through a physiological and transcriptome reprogramming when the alga is grown with organic nutrients casein amino acids, but not with inorganic nutrients. SSB01 grows at a faster rate and maintains stable photosynthetic efficiency when supplemented with casein amino acids compared to only inorganic nutrients or seawater. These physiological changes are driven by massive transcriptome changes in SSB01 when supplemented with casein amino acids. Transcripts involved in DNA conformation changes such as DNA topoisomerases, histones, and genes involved in structural maintenance of chromosomes were all significantly changed. Functional enrichment analysis also revealed processes involved in translation, ion transport, generation of second messengers, and phosphorylation. Conversely, few transcriptional changes were observed when cultured with inorganic nutrients. The physiological and molecular changes that underlie in vitro trophic transitions in Symbiodiniaceae track with changes that occur during cnidarian-algal symbiosis and can serve as an orthogonal platform to further understand this critical symbiosis.